Severe hypercalcemia in elderly patient with asymptomatic pulmonary tuberculosis: a case report - Manoela Barros; Sarah Francisco; Julia Vieira; Rafael Costa; Luciene Motta; Cristiano Barros; Decio Sesquim; Alessandra Tieppo; Caroline Pupim; Renato Lirio Morelato (Geriatric Care, 2023)
Hypercalcemia presents itself as a challenging disorder in clinical practice, with hyperparathyroidism and malignancies accounting for 90% of the causes. The case report describes a married 78-year-old white rural male worker with low level of education. Given the social isolation brought on by the COVID-19 pandemic, the patient initially received antidepressants for a history of adynamia, muscle weakness, and inappetence for a year. Four months before admission, he had an aggravation of the clinical picture, presenting mental confusion, and becoming dependent for all daily life activities. He was hospitalized with adynamia and intense fatigue, muscle weakness, inappetence with weight loss, splenomegaly and severe hypercalcemia (15.9 mg/mL; corrected by serum albumin - reference value: 8.8 to 10.3 mg/dL) and low parathyroid hormone level. This is a rare case of severe hypercalcemia in an elderly patient with asymptomatic pulmonary tuberculosis with late diagnosis and renal impairment, possibly aggravated by hypercalcemia.